Work-related injuries and illnesses among kitchen workers at two major students' hostels - Ghada O. Wassif; Abeer Abdelsalam; Waleed Salah Eldin; Mona A. Abdel-Hamid; Samia I. Damaty (SpringerOpen, 2024)
Abstract Background Kitchen workers face a disproportionately high risk of injuries and illnesses. Yet, despite the ubiquity of kitchen-related injuries, there has been a relative lack of comprehensive research on this topic, particularly in developing countries. Ain Shams University, as a prestigious educational institution with its diverse kitchen staff, provides an ideal setting for studying the challenges faced in professional kitchens. This study aims to measure the prevalence of work-related injuries and illnesses among kitchen workers of two major students' hostels at Ain Shams University in Cairo and to explore their risk factors. Methods A cross-sectional analytical study involving kitchen staff from two hostels that house students at the university was carried out in 2021. The study involved all kitchen staff in the dorms for students (n = 128). Data was collected using a structured interview questionnaire. Results The findings showed a significant prevalence of work-related illnesses (81.3%) and injuries (77.3%) among restaurant employees. Age, education, and job type all had a statistically significant relationship with the frequency of work-related injuries over the previous year. Additionally, there was a statistically significant relationship between age, job type, and the frequency of diseases among kitchen workers (p ≤ 0.05). Conclusion Cooks and other food service employees are more susceptible to occupational diseases and injuries in the workplace. Restaurants and the university hostel authorities should implement preventative measures and policies to lower the risk of harm among these employees by offering occupational health and safety services such as training and education programs, personal protective equipment, and regular health examinations.